Conservative Management of Tubo-ovarian Abscess through Minimal Invasive Route: A Case Report - Amey Chugh; Janvi Patel; Prashansa Gupta; Varshini Vadithala (Journal of Clinical and Diagnostic Research)
Tubo-ovarian Abscess (TOA) is a challenging infectious condition of the adnexa, typically arising from Pelvic Inflammatory Disease (PID). Patients with TOA commonly present with symptoms such as lower abdominal pain, fever and vaginal discharge. Traditionally, cases of TOA have been addressed through total abdominal hysterectomy. TOA typically presents with abdominal pain and fever, which, on imaging, appear as a lobulated multicystic lesion in the adnexa. These cases were managed through transvaginal aspiration, resulting in a satisfactory outcome. The present report of a 45-year-old woman emphasises the efficacy of management through minimally invasive techniques and highlights the role of interventional radiology in managing such cases.